(3GdMdd aj TQM CHjGJ GdMeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj YdefG eGde fcf fYde deG aQZJ ef GdcdGe aj GUWdGM GdNdd GdhGbY aj cJGH GdMed GQOJ Cf GJHY Pdc GdcdGe aj GYQGH GHjGJg heYGfjgG s
(3BNQgG (B:s
(3hgh ZjQ ehGa ddHjJ dCfg dG hLg ajg dPcQ GdYRdI EdG Ydj GdJaSjQ GdChd hhbY aj fSNI cJGH SjHhjI GdJj QhGgG GHh HcQ gPG GdHjJ Ydi QhGjI CNQj s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B121s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs